2022
DOI: 10.1038/s41523-022-00387-0
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor beta repurposes EZH2 to suppress oncogenic NFκB/p65 signaling in triple negative breast cancer

Abstract: Triple Negative Breast Cancer (TNBC) accounts for 15–20% of all breast cancer cases, yet is responsible for a disproportionately high percentage of breast cancer mortalities. Thus, there is an urgent need to identify novel biomarkers and therapeutic targets based on the molecular events driving TNBC pathobiology. Estrogen receptor beta (ERβ) is known to elicit anti-cancer effects in TNBC, however its mechanisms of action remain elusive. Here, we report the expression profiles of ERβ and its association with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 82 publications
(90 reference statements)
0
23
0
Order By: Relevance
“…A molecular study demonstrated that the MafG promoter contained AP-1, E-box, and NF-κB binding sites. The transcription factors p50, p65, AP-1 family (c-Jun, c-Fos, Fos-B, Fra-1, Fra-2) and c-myc are recognized as oncogenes due to their capacities to maintain malignant cell survival and offer signals for unlimited proliferation [50][51][52]. These transcription factors are highly expressed in esophageal cancer, prostate cancer and gastric cancer [53][54][55].…”
Section: Regulation Of Mafs At the Transcriptional Levelmentioning
confidence: 99%
“…A molecular study demonstrated that the MafG promoter contained AP-1, E-box, and NF-κB binding sites. The transcription factors p50, p65, AP-1 family (c-Jun, c-Fos, Fos-B, Fra-1, Fra-2) and c-myc are recognized as oncogenes due to their capacities to maintain malignant cell survival and offer signals for unlimited proliferation [50][51][52]. These transcription factors are highly expressed in esophageal cancer, prostate cancer and gastric cancer [53][54][55].…”
Section: Regulation Of Mafs At the Transcriptional Levelmentioning
confidence: 99%
“…For example, a recent study looking into a cohort of 567 TNBC tumors, found that ERβ was expressed in 18% of them. Possible mechanisms for ERβ mediated tumor suppression include the formation of co-repressor complexes that suppress the activity of oncogenic NFκB/RELA (p65) and thus inhibit p65 signaling ( 75 ). Additionally, Erβ has been found to downregulate the unfolded protein response (UPR), which enables the survival of cancer cell to endoplasmic reticulum stress induced by poor tumor vascularization ( 76 ).…”
Section: The Human Microbiome and Cancermentioning
confidence: 99%
“…Numerous studies have reported the expression of a second form of the estrogen receptor, estrogen receptor beta (ERβ), in TNBC (6). Using a highly validated monoclonal antibody (7,8), we and others have demonstrated that ERβ1, the full length form of this receptor, is expressed in approximately 20% of primary TN breast tumors (6,(8)(9)(10). Tumoral expression of ERβ is generally associated with better prognostic factors such as lymph node negativity, enhanced responses to therapy, and improved patient outcomes such as improved diseasefree, metastasis-free, and overall survival (6,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Using a highly validated monoclonal antibody (7,8), we and others have demonstrated that ERβ1, the full length form of this receptor, is expressed in approximately 20% of primary TN breast tumors (6,(8)(9)(10). Tumoral expression of ERβ is generally associated with better prognostic factors such as lymph node negativity, enhanced responses to therapy, and improved patient outcomes such as improved diseasefree, metastasis-free, and overall survival (6,(10)(11)(12)(13). Ligand-mediated activation of ERβ has been shown to decrease proliferation, invasion, and migration of TNBC cells in vitro as well as tumor formation, growth, and metastatic spread in vivo (10,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation